Genetic Characterization of Sumatran Mirah Chicken Based on Mitochondrial D-loop Region Sequence - Silalahi, Parsaoran; Sitorus, Tunggul Ferry; Putra, Widya Pintaka Bayu (HAYATI Journal of Biosciences, 2025)
Mirah chickens are Indonesian indigenous chickens that originate from Simalungun Regency, North Sumatera Province of Indonesia. The study aimed to determine the genetic characterization of Mirah chicken based on the mitochondrial D-loop region (838 bp). Twenty Mirah cocks from Simalungun Regency of Indonesia were used in the present study. The results showed that fourteen haplotypes were found in the studies of birds based on sixteen mutation sites. Therefore, these haplotype and nucleotide diversities in the partial D-loop region of the Mirah chicken were classified as high. The Median-joining tree revealed that the Mirah chickens were classified in a similar cluster with the Red jungle fowl (Gallus gallus). Ten haplotypes of birds were close to G. g. bankiva, and four haplotypes of birds were close to G. g. gallus. In conclusion, Mirah chickens had the genetic introgression from two sub-species of Red junglefowl, i.e., G.g. gallus and G.g. bankiva. Hence, the pure breeding program for Mirah chickens is important to conserve their genetic resources from extinction.